2013
DOI: 10.1002/anie.201304276
|View full text |Cite
|
Sign up to set email alerts
|

Sandmeyer Trifluoromethylation of Arenediazonium Tetrafluoroborates

Abstract: Copper capabilities: Diazonium salts are converted into the corresponding trifluoromethyl derivatives in the presence of a trifluoromethyl–copper complex generated in situ from CuSCN and the inexpensive, easy‐to‐use trifluoromethylating reagent Me3Si‐CF3 (see scheme). This Sandmeyer‐type reaction allows the straightforward synthesis of trifluoromethylated arenes and heteroarenes from the corresponding amines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
54
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(58 citation statements)
references
References 60 publications
(29 reference statements)
1
54
0
Order By: Relevance
“…trifluoromethylation and trifluoromethylthiolation of arenediazonium tetrafluoroborates have also been reported recently. [21,22] It may also be noted that the direct reaction of diazonium salts with amines, which proceeds by a radical mechanism, has also been reported in the literature. [23] Some of us [24] recently reported the first copper-catalyzed C-N bond-formation reaction involving arenediazonium salts.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…trifluoromethylation and trifluoromethylthiolation of arenediazonium tetrafluoroborates have also been reported recently. [21,22] It may also be noted that the direct reaction of diazonium salts with amines, which proceeds by a radical mechanism, has also been reported in the literature. [23] Some of us [24] recently reported the first copper-catalyzed C-N bond-formation reaction involving arenediazonium salts.…”
Section: Introductionmentioning
confidence: 82%
“…The Cu I catalyst reacts with the diazonium salt according to either (a) an oxidative addition [49][50][51] or (b) a single-electron transfer [21,22,52] (SET; from the metal species or from another reductive agent source) with loss of the N 2 group as a gas. The choice between paths (a) and (b) is usually motivated by a radical-clock experiment or by a control experiment in the presence of a radical scavenger.…”
Section: The Active Copper Speciesmentioning
confidence: 99%
“…In 2013, Dai et al, 70 Danoun et al, 71 and Wang et al 72 reported the Sandmeyer-type trifluoromethylation of aryl diazonium salts (Figure 32). Although these reactions are carried out similarly, different mechanisms have been proposed in their reports.…”
mentioning
confidence: 99%
“…In particular, trifluoromethylated compounds are characterized by superior metabolic stability, binding selectivity, bioavailability and lipophilicity compared with those of their nontrifluoromethylated analogues, and these characteristics have stimulated the intensive development of new pharmaceutical and agrochemical agents bearing this moiety [3][4][5] . In general, transition-metal-catalysed cross-coupling reactions (for example, those involving Cu, Pd, Ru or Ir) are regarded as state-of-the-art methods for C-CF 3 bond formation [6][7][8][9][10][11][12][13][14][15][16][17][18] . However, these transition-metal-catalysed reactions pose their own challenges.…”
mentioning
confidence: 99%